Cervical & thoracic manipulations: Acute effects upon pain pressure threshold and self-reported pain in experimentally induced shoulder pain. (February 2016) - Wassinger, Craig A.; Rich, Dustin; Cameron, Nicholas; Clark, Shelley; Davenport, Scott; Lingelbach, Maranda; Smith, Albert; Baxter, G. David; Davidson, Joshua
Abstract: Background: Emerging evidence suggests that cervical and thoracic joint manipulations may be advocated in treating patients with shoulder pain. Objectives: To determine the acute effects of cervical, cervicothoracic, and thoracic joint manipulations on outcomes of self-reported pain and pain pressure threshold in experimentally induced shoulder pain. Design: Repeated measures. Methods: Twenty (20) healthy volunteers were tested on two sessions. Session 1 consisted on baseline assessment of pain pressure threshold testing over the infraspinatus bilaterally and self-reported shoulder pain using the shoulder pain and disability index (SPADI) pain scale. An isokinetic exercise protocol was used to induce delayed onset muscle soreness. In session 2 (24–48 h later), all variables were reassessed before and immediately after a combination of cervical, cervicothoracic and thoracic manipulations. Results: SPADI pain scale scores were significantly different between time points ( p < 0.001): the exercise protocol significantly increased reported pain [mean increase 14.1, p < 0.001] while the manipulation significantly decreased reported pain (mean decrease 5.60, p < 0.001)) although pain remained higher than baseline levels. Pain pressure threshold differences were also found between time points ( p = 0.001): manipulation significantly increased pain threshold bilaterally ( p < 0.001) similar to baseline levels. Conclusions: Cervical, cervicothoracic, and thoracic joint manipulations acutely increased pain pressure threshold and decreased self-reported shoulder pain in participants with experimentally induced shoulder pain. Physiotherapists may consider the combination of such techniques to achieve short-term hypoalgesic effects and facilitate the application of more active interventions. Highlights: We examined the effect cervical and thoracic manipulations on experimental shoulder pain. An external rotation eccentric exercise protocol caused mild shoulder pain. Self-reported shoulder pain was reduced immediately following manipulations. Pain pressure threshold over infraspinatus increased bilaterally after manipulations.